Performance of CdS/TNTAs Nanocomposite in Removing Ciprofloxacin and Hydrogen Production using Simultaneously Electrocoagulation-Photocatalysis Process - Rahayu Lestari Sugihartini; Reno Pratiwi; Slamet Slamet (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
This study used CdS as a pair of TiO2 Nanotube Arrays (TNTAs), considering the position and width of the energy band gap, which is expected to increase photocatalyst performance. The nancomposite was synthesized using the successive ionic layer adsorption reaction (SILAR) method, with Cd(CH3COO)2 and Na2S as precursors. The CdS/TNTAs nanocomposite is expected to reduce the energy band gap to enable the visible and UV spectrum to activate the photocatalyst. Additionally, the formed heterojunction mechanism provides opportunities for the trajectories of electrons and holes to be farther apart and reduce the recombination rate. The degradation ability of CdS/TNTAs nanocomposite in the photocatalytic process was evaluated using samples of ciprofloxacin liquid waste as an antibiotic, which is quite challenging to decompose completely. The ability of the photocatalytic process to produce hydrogen gas was also observed and its performance synergized with the electrocoagulation process. The result showed that the use of CdS as a TNTAs partner in CdS/TNTAs nanocomposites affects increasing photocatalyst performance, both in degrading ciprofloxacin and producing hydrogen gas. Furthermore, the CdS/TNTAs nanocomposite increased the photocatalytic process’s ability to degrade ciprofloxacin and produce hydrogen from 8.5 to 20.5% and 6 to 23.5 mmol/m2 compared to using TNTAs alone. The processing capability is further enhanced when run in synergy with the electrocoagulation process where the removal of ciprofloxacin reaches 86.55%  and the hydrogen produced is 2.62×106 mmol/m2. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).